PERBEDAAN HASIL BELAJAR PENDIDIKAN AGAMA ISLAM DENGAN STRATEGI PEMBELAJARAN AKTIF TIPE TEAM QUIZ DAN PRACTICE REHEARSAL PAIRS PADA SISWA KELAS X SMK NEGERI 1 SEI RAMPAH KABUPATEN SERDANG BEDAGAI - Elly Pasaribu (Universitas Islam Negeri Sumatera Utara Medan, 2017)
The purpose of this research is to know: (1) the influence of an active learning strategy of tean quiz type to the student learning outcomes in Islamic religious education lesson, (2) the influence of the active learning strategy of type Practice Rehearsal Pairs on student learning outcomes in Islamic religious education lesson which taught by Active learning strategy of tean quiz type and learning result of Islamic religious education which taught by the active learning strategy type Practice Rehearsal Pairs. The study population is all students of class X of computer and network engineering majors in public vocational high school 1 Sei Rampah Serdang Bedagai regency which amounted to eighty students. The technique of sampling is done by cluster random sampling technique, that is random sampling of clump which means that all the individuals in the sample class will be the subjects of the research. The technique of collecting data is by using a test, while the data analysis technique using t test at the significance level α = 0.05. The findings of the research are: (1) there is an influence on the learning outcomes in Islamic religious education which is taught by the active learning strategy of tean quiz type on the material verses of al qur'an about democracy. This is tested by t-test statistical calculation t obtained value tcount = 3.47 while ttable value = 2.0231, (2) there is an influence on learning outcomes in Islamic religious education taught by the active learning strategy type Practice Rehearsal Pairs on the material of al Qur’an verses on democracy. This is tested by t-test statistic t calculation tcount value = 5.28 while the value ttable = 2.0231, and (3) there is a significant difference in the learning results of Islamic religious education is taught with active team learning strategy team quiz type and active learning strategy Type Practice Rehearsal Pairs on the material verses of al qur'an about democracy. This is true tested through t test statistical calculation tcount value = 3.00 while the value of ttable = 2.0231. Then seen from the average learning outcomes then the results of learning on Islamic religious education taught by team strategy quiz = 17, 85 higher than the average learning outcomes in Islamic religious education taught with practice strategy rehearsal pairs = 16.35